Comparative Phytochemical And Antibacterial Studies On The Bark Of Wrightia Tinctoria And Wrightia Arborea - M. S. KHYADE; N. P. VAIKOS (International Journal of Pharma and Bio Sciences, 2011)
Comparative phytochemical and antibacterial activities of bark of Wrightia tinctoria and Wrightia arborea were investigated. The bark extracts showed the presence of alkaloids, phenolics, saponins and tannins in both the species. The antibacterial activities of bark of W. tinctoria and W. arborea in successive different solvent were tested against gram +ve and gram -ve organisms. The chloroform extracts of W. arborea showed the broader spectrum of antibacterial activity when compared with W. tinctoria. However, Wrightia tinctoria is a widely used medicinal plant.